2021
DOI: 10.3991/ijet.v16i10.19679
|View full text |Cite
|
Sign up to set email alerts
|

Management Priorities of Audiovisual Student Projects during the COVID-crisis

Abstract: COVID-crisis has made significant changes in the educational process of many coun-tries, including the need for new management decisions that would solve the complex problem of accelerating the development of online resources for distance learning. Management, particularly in education, is valuable when it is able to combine both general and specific goals. Especially when it comes to a specific educational process for training future TV and radio journalists, advertisers and PR-managers, screenwrit-ers and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
(8 reference statements)
0
4
0
4
Order By: Relevance
“…The medical students showed a preference to virtual learning over physical learning most probably due to the fact that students easily attend classes at a convenient time and can hear the recorded lectures many times and virtually perform practical [29]. In the midst of the COVID-crisis, Goian, et al [30] developed a successful distance educational approach, which had a direct impact on the quality of practical training of experts in the field of audio-visual media and arts. Maskati, et al [31] also reported that virtual reality is a new method that has shown to be beneficial in both teaching and entertainment.…”
Section: The Covid-19 Pandemic and Online Learningmentioning
confidence: 99%
“…The medical students showed a preference to virtual learning over physical learning most probably due to the fact that students easily attend classes at a convenient time and can hear the recorded lectures many times and virtually perform practical [29]. In the midst of the COVID-crisis, Goian, et al [30] developed a successful distance educational approach, which had a direct impact on the quality of practical training of experts in the field of audio-visual media and arts. Maskati, et al [31] also reported that virtual reality is a new method that has shown to be beneficial in both teaching and entertainment.…”
Section: The Covid-19 Pandemic and Online Learningmentioning
confidence: 99%
“…El uso de las redes sociales virtuales durante la crisis sanitaria producto del COVID-19, han sido vitales para el intercambio de contenidos y se consideran como una poderosa herramienta comunicacional de soporte para el aprendizaje de los estudiantes que hacen uso de diversas plataformas para la interacción sincrónica y asincrónica (Goian et al, 2021). De esta manera, el estudiante ha incorporado las TIC como una herramienta fundamental para el intercambio de material multimedia y audiovisual como un recurso interactivo donde ha aprendido a obtener, procesar y crear información.…”
Section: Desarrollounclassified
“…Marcos y Moreno (2020) dan a conocer en su disertación que los recursos audiovisuales suelen ser una innovadora y creativa forma de llevar conocimiento en especial para el público joven cuyo consumo de productos audiovisuales desde películas hasta spots publicitarios genera nuevos contenidos conceptuales como actitudinales. Del mismo modo, Goian et al (2021) menciona que los productos audiovisuales vertidos a través del cine, televisión e internet han servido como un componente tecnológico educativo durante la crisis del COVID-19.…”
Section: Introductionunclassified
“…Learning from home can run effectively when supported by adequate learning facilities and tools such as internet access, textbooks, and online learning systems that teachers and students can use [6]. In addition, it requires the quality of exciting and adequate learning media to support the learning process [7].…”
Section: Introductionmentioning
confidence: 99%